Peningkatan Daya Layan Sekolah dan Pembelajaran Dengan Layanan Google - Situmorang, Sudirman (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The purpose of this study is to integrate Google services to improve school service capacity, namely school management and learning carried out by teachers. Google services that are applied in this best practice are Gmail, Google Drive, Google Calendar, and Google Classroom. This research was carried out in Simanindo 4 Public Middle School in the 2015/2016 learning year. From the results of implementing this Google Service, obtained an increase in school management and learning services, namely (1) the average knowledge and competence about Google services is sufficient, and (2) the cumulative percentage of service descriptions, namely (a) not good 18.80 %, (b) good enough 65.35%, (c) good (24.52%), and (d) very good (10.13%). Keywords: Google services, management, schools, learning Abstrak: Tujuan penelitian ini adalah pengintegrasian layanan Google untuk meningkatkan daya layan sekolah yaitu pengelolaan sekolah dan pembelajaran yang dilaksanakan oleh para guru. Layanan Google yang diaplikasikan dalam praktik terbaik ini adalah Gmail, Google Drive, Google Calendar, dan Google Classroom. Penelitian ini dilaksanakan di SMP Negeri 4 Simanindo pada tahun pembelajaran 2015/2016. Dari hasil penerapan ini Layanan Google, diperoleh peningkatan daya layan pengelolaan sekolah dan pembelajaran yaitu (1) rata-rata pengetauan dan kompetensi tentang layanan Google adalah cukup, dan (2) rata-rata persentase kumulatif dari deskripsi layanan yaitu (a) kurang baik 18.80%, (b) cukup baik 65.35%, (c) baik (24.52%), dan (d) sangat baik (10.13%). Kata kunci: layanan Google, pengelolaan, sekolah, pembelajaran